USING STORYTELLING TO INCREASE SPEAKING PERFORMANCE OF PAI STUDENTS OF MUHAMMADIYAH UNIVERSITY OF METRO - Amirudin - Latif (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2013)
The study is intended to increase speaking performance of PAI students of Muhammadiyah University of Metro by using storytelling. The design of the research is collaborative classroom action research which involves a collaborator in whole process of the research. The instruments of the research are observation sheet, field notes, and speaking test. The criteria of success of the research are 100% from thirty students are active in the classroom and get score equal to or more than 70. The result shows that twenty two students get score 70 in Cycle 1 and thirty in Cycle 2.